Self Esteem Inventory for adult ALPEL FORMA - AD - Loli Pineda, Alejandro E. (2001)
An Inventory of Self-esteem is presented for Adults, conceived for the organizational environment there being you considered as components of the Self-esteem to: self-realization, self-knowledge, self-respect, and self-confidence. The definitive form is product of a first stage of Approach of Judges and the validity and statistical reliability. It is of collective application and singular and it presents scales for different ages.